Client-Perpetrated Violence Among Frontline Child Welfare Workers - Radey, Melissa (Journal of interpersonal violence, 2021)
Client-perpetrated violence against child protective services (CPS) workers is common and detrimental to worker wellbeing with consequences including physical injury and psychological illnesses. Despite the impacts of violence, few studies capture violence in a representative sample of CPS workers. This study examines prevalence and applies a structural inequality framework to consider who among CPS workers is most susceptible. This article used the Florida Study of Professionals for Safe Families dataset, a longitudinal panel study of newly hired CPS workers (N = 1,501) to examine the prevalence of violence in the first 6 months of employment and consider the influence of individual characteristics. CPS workers experienced high levels of non-physical violence (75%), threats (37%), and physical violence (2.3%). Age and race were significantly related to instances of violence as were college major and position. Relationships were nuanced and did not uniformly follow a structural inequality framework. The high prevalence of violence within the first months on the job illustrates the importance of conflict and violence training before workers acquire independent caseloads. In addition, institutionalized mandatory reporting procedures with definitions of non-physical violence, threats, and physical violence may promote a culture of safety rather than an attitude that violence is part of the job. Finally, supervisors and peers can benefit from opportunities to support one other. The high prevalence of violence within certain subgroups of workers coupled with its wide-ranging consequences call for additional theoretical and empirical research and responsive policy to prioritize worker safety and wellbeing.